Spain the trials and triumphs of a modern European country - Reid, Michael (Yale University Press, 2023)
An incisive account of modern Spain, from the death of Franco to the Catalan referendum and beyond Spain's transition to democracy after Franco's long dictatorship was widely hailed as a success, ushering in three decades of unprecedented progress and prosperity. Yet over the past decade its political consensus has been under severe strain. A stable two-party system has splintered, with disruptive new parties on the far left and far right. No government has had a majority since 2015. Michael Reid overturns the stereotypical view of Spain as a country haunted by its Francoist past. From Catalan separatism and the indignados movement to the Spanish economy's overdependence on tourism and small business, Spain's challenges can often seem unique. But Reid is careful to emphasize the many pressures it faces in common with its European neighbors--such as austerity, populism, and increasing polarization. The result is a penetrating yet rounded portrait of a vibrant country--one that is more often visited than understood.
Keywords: Spain -- History -- 1975-; Spain -- Politics and government -- 1975-1982.; Spain -- Politics and government -- 1982-; Spain -- Social conditions -- 1975-; Spain -- Politics and government -- 21st century.; Spain -- History -- 21st century.; Espagne -- Histoire -- 1975-; Espagne -- Politique et gouvernement -- 1975-1982.; Espagne -- Conditions sociales -- 1975-; Espagne -- Politique et gouvernement -- 21e siècle.; Espagne -- Histoire -- 21e siècle.; History -- Europe -- Spain & Portugal.; History -- Modern -- 20th Century.; History -- Modern -- 21st Century.; Politics and government; Social conditions; Spain; Since 1975; History